DAMPAK PANDEMI COVID-19 BAGI PEKERJA “PHK, PEMOTONGAN GAJI, DAN MOTIVASI KERJA” - Yahya Achiel; Balgies Soffy; Audisya Amanda Eka; Jati Ratih Kumaya (PSIKOWIPA (Psikologi Wijaya Putra), 2020)
Covid-19 pandemic has effected on all sectors of human life, especially in the industrial economy sector which results in the widespread phenomenon of termination of employment. Companies that have terminated their work relations and cut wages for their employees need to pay attention to the Indonesian labor laws. Besides, termination of employment results in the practice of transferring duties to other employees who are still surviving. However, the transfer of duties that occurred was not accompanied by an increase in employee salaries. This situation can result in reduced motivation and work productivity of employees. This paper will examine the phenomenon of termination of employment and its impact on employees and companies during the Covid-19 pandemic.